(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the peculiarities of stylistic variation in speech acts of moral support within English linguoculture. The study analyzes linguistic means and communicative strategies employed by native speakers of English to express sympathy, encouragement, consolation, and emotional support in various communicative situations. Particular attention is paid to the influence of social context, degree of formality, and cultural norms on the choice of lexical, syntactic, and pragmatic means of expressing support. The research demonstrates that the stylistic diversity of speech acts of moral support contributes to effective interpersonal communication and reflects the value orientations of English-speaking society.